Osteoclasts adapt to physioxia perturbation through DNA demethylation. (18th October 2021) - Nishikawa, Keizo; Seno, Shigeto; Yoshihara, Toshitada; Narazaki, Ayako; Sugiura, Yuki; Shimizu, Reito; Kikuta, Junichi; Sakaguchi, Reiko; Suzuki, Norio; Takeda, Norihiko; Semba, Hiroaki; Yamamoto, Masamichi; et al.
Abstract: Oxygen plays an important role in diverse biological processes. However, since quantitation of the partial pressure of cellular oxygen in vivo is challenging, the extent of oxygen perturbation in situ and its cellular response remains underexplored. Using two‐photon phosphorescence lifetime imaging microscopy, we determine the physiological range of oxygen tension in osteoclasts of live mice. We find that oxygen tension ranges from 17.4 to 36.4 mmHg, under hypoxic and normoxic conditions, respectively. Physiological normoxia thus corresponds to 5% and hypoxia to 2% oxygen in osteoclasts. Hypoxia in this range severely limits osteoclastogenesis, independent of energy metabolism and hypoxia‐inducible factor activity. We observe that hypoxia decreases ten‐eleven translocation (TET) activity. Tet2/3 cooperatively induces Prdm1 expression via oxygen‐dependent DNA demethylation, which in turn activates NFATc1 required for osteoclastogenesis. Taken together, our results reveal that TET enzymes, acting as functional oxygen sensors, regulate osteoclastogenesis within the physiological range of oxygen tension, thus opening new avenues for research on in vivo response to oxygen perturbation. Synopsis: Within the physiological range of oxygen tension, ten‐eleven translocation (TET) enzymes act as functional oxygen sensors involved in osteoclastogenesis. Oxygen tension ranges from 17.4 to 36.4 mmHg in osteoclasts of live mice. Hypoxia in this range decreases TET activity of osteoclasts but does not affect energy metabolism and HIF activity. Tet2/3 regulate osteoclastogenesis by controlling Prdm1 expression via oxygen‐dependent DNA demethylation. Abstract : Within the physiological range of oxygen tension, ten‐eleven translocation (TET) enzymes act as functional oxygen sensors involved in osteoclastogenesis.